EFFORTS TO INCREASE PUBLIC KNOWLEDGE ABOUT DIGITAL MARKETING AS ONE OF THE EFFORTS TO IMPROVE THE FAMILY ECONOMY - Tayo, Yanti; Nursanti, Siti; Utamidewi, Wahyu; Farni Syammaella, Nur’annafi; Nurfauziyah, Sabrina; Febylania, Alisha (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The use of smartphones has increased significantly since the COVID-19 pandemic. This is due to the government's policy of restricting human-to-human gatherings in order to avoid the transmission of the COVID-19 virus. People's lives are being made easier as communication and information technology advances; the world appears to be shrinking, and distance and time are no longer obstacles to humans meeting their needs. Technological advancements must be accompanied by an increase in the community's ability to use technology in order for it to be used optimally, particularly in efforts to improve the family economy. This community service aims to increase public awareness of the use of Internet-based media for digital marketing purposes. Community service is accomplished through direct exposure, discussion, and practice. This study was followed by mothers and women in the Waluya village. The information provided was about digital marketing and how to use it to improve the family economy by starting a home-based industry-based business. Mothers and women in Waluya Village are becoming more knowledgeable, and there is a greater interest in starting an online store to help the family economy.